"Hagia Chora": Von einem neuerdings wieder erhobenen geomantischen Ton in der Geographie - Hard, Gerhard (ERDKUNDE, 2001)
This article attempts a literary and historical contextualization of Falter & Hasse (in this issue). F&H connect in a idiosyncratic way the relics of two well-known vocabularies and world views: Critical Theory and Revolutionary Conservatism. The authors associate these apparently contradictory vocabularies and political philosophies with the symbolic and emotional meaning of landscape. For the most part the article of F&H indulges in a revitalisation of some central rhetorical figures of traditional German Landscape Geography. The authors’ New Landscape Approach lists mostly the common sense connotations of the German word Landschaft, it collapses clearly sensuous, intuitive, scientific, moral, religious knowledge as well as self-knowledge, and implies among others a sort of landscape racism. The authors’ interpretions of the landscape photographs are fundamentally questioned. In the last part of the article the authors’ proposals for a future geography and nature conservation are discussed.